PENJATUHAN HUKUMAN MELAMPAUI UNSUR JARIMAH PEMERKOSAAN DALAM PERSPEKTIF ASAS LEGALITAS - Mansari Mansari; Fauziati Fauziati; Khairuddin Khairuddin (Komisi Yudisial RI, 2025)
This study examines Judgment Number 26/JN/2024/MS.Bna, which imposed a sentence of 150 months’ imprisonment for the jarimah/offense of rape against a child under Article 50 of the Qanun Jinayat. This case warrants further analysis because the facts established at trial support only the offense of sexual harassment committed by an adult against a child under Article 47 of the Qanun Jinayat. The main constituent elements of rape, namely the use of violence, coercion, or threats, were not established at trial, nevertheless, the defendant was convicted under the legal classification of rape. This circumstance raises significant concerns relating to the proper application of the law, legal certainty, and the administration of justice. This study aims to analyze the imposition of a sentence without satisfying the constituent elements of the offense of rape and to assess the judgment from the perspectives of legal certainty, justice, and victim protection. This study employs a normative legal research method with a case-study approach. Data were collected through an analysis of judgments, a review of relevant legal literature, and interviews with legal practitioners. The findings indicate that the sentence imposed is legally improper and violates the principle of legality because it was imposed without satisfying the constituent elements of rape as prescribed under Article 50 of the Qanun Jinayat. The facts established at trial demonstrate the existence of enticement, which does not constitute an element of rape under the jinayat law. This judgment does not reflect legal certainty and justice for the offender, although, from the perspective of victim protection, it may be regarded as providing a sense of security. This study recommends the reformulation of Article 50 of the Qanun Jinayat by clarifying the legal classification of child rape through the incorporation of deception or enticement as constituent elements, in order to promote justice and child protection in Aceh.